Semantic component of speech development of older preschoolers in the process of speech education - Yuri A. Kochetkov; Oksana S. Ushakova (Современное дошкольное образование)
Background. Modern society places high demands on the level of language training of children, starting from an early age, which makes it relevant to search for effective methods of speech development and children’s awareness of the phenomena of language and speech. The problem of speech development in the process of speech education at the stage of preschool childhood involves a new consideration of the issues of children’s respect for their native language, which is due to the importance of mastering its national specifics, familiarization with the language as a national treasure. In addition, the development of semantics in speech contributes to the general intellectual development of children, laying the foundation for the subsequent development of more complex language structures and concepts.